2016
DOI: 10.1002/jcp.25299
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Autonomous Brown‐Like Adipogenesis of Preadipocytes From Retinoblastoma Haploinsufficient Mice

Abstract: Mechanisms behind the emergence of brown adipocyte-like (brite or beige) adipocytes within white adipose tissue (WAT) are of interest. Retinoblastoma protein gene (Rb) haploinsufficiency associates in mice with improved metabolic regulation linked to a greater capacity for fatty acid oxidation and thermogenesis in WAT. We aimed to explain a feasible mechanism of WAT-to-BAT remodeling in this model. Differentiated primary adipocytes and Sca1-positive preadipocytes derived from adipose depots of Rb(+/-) mice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…This cell-autonomous function of pRb, increasing the capacity for brown-like adipogenesis, was confirmed in recent studies (Hu et al, 2015;Petrov et al, 2016). Altogether, GATA, pRb, and E2F1 are intrinsically involved in adipogenesis.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…This cell-autonomous function of pRb, increasing the capacity for brown-like adipogenesis, was confirmed in recent studies (Hu et al, 2015;Petrov et al, 2016). Altogether, GATA, pRb, and E2F1 are intrinsically involved in adipogenesis.…”
Section: Introductionsupporting
confidence: 57%
“…Overall, the data presented here indicate that disruption of the LXCXE pRb-binding site of FOG-2 in adipocyte progenitors may induce WAT browning, providing support for a role of pRb in directing the differentiation of bipotent adipocyte precursors into white or brown adipocytes. This hypothesis is not new, and retinoblastoma protein haploinsufficiency (Mercader et al, 2009;Petrov et al, 2016), disruption (Calo et al, 2010;Dali-Youcef et al, 2007;Hansen et al, 2004), and indirect inhibition (Hu et al, 2015;Scimè et al, 2005;Wang et al, 2013) have identified pRb as a regulator of the commitment of preadipocytes to brown adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that CTS, COST, and COSM may activate UCP1 in a PKA-MAPK-dependent manner and in a PKA-MAPK-independent manner (Supplementary Figure S2C) [33]. In addition, the lipid metabolism genes, Slc27a1 and TMEM26, which are specifically expressed in beige fat [34], are also increased with CTS, COST, and COSM treatment. The increased expression of these genes indicates an increase in WAT browning and thermogenesis, which become key strategies for addressing obesity.…”
Section: Discussionmentioning
confidence: 65%
“…As shown in Fig. S2E, solute carrier family 27 member 1 (Slc27a1, also known as Fatp1) was increased 2.7-fold and transmembrane 26 (Tmem26) and short stature homeobox-2 (Shox2) were significantly decreased in eWAT of PDE3B KO mice21848586.…”
Section: Discussionmentioning
confidence: 89%